Associations of single nucleotide polymorphisms in candidate genes with the polled trait in Datong domestic yaks. (27th August 2013) - Liu, W. B.; Liu, J.; Liang, C. N.; Guo, X.; Bao, P. J.; Chu, M.; Ding, X. Z.; Wang, H. B.; Zhu, X. S.; Yan, P.
Summary The domestic yak (Bos grunniens) is an iconic symbol of animal husbandry at high altitudes. Yaks exhibit unique external characteristics including long hair and large horns. However, hornless yaks can be found in different breeds and different populations. The hornless trait is also known as polled, and the POLL locus has been fine‐mapped to chromosome 1 in cattle (Bos taurus), although the underlying genetic basis of the polled trait is still unclear in the yak. Thus, we performed an association study to identify the genetic polymorphisms responsible for the polled trait in the yak. Fifty polled Datong domestic yaks and 51 horned individuals were selected randomly from a huge herd and were used as the case and control groups respectively for the association analysis. Twelve genes located in the candidate region of the POLL locus in cattle were used as references to detect DNA polymorphisms related to yak polledness, which were analyzed by sequencing and a high‐resolution melting test. We applied Fisher's exact test and haplotype analysis to show that a 147‐kb segment that included three protein‐coding genes C1H21orf62, GCFC1 and SYNJ1 was the most likely location of the POLL mutation in domestic yaks.